Can the vaccine adverse event reporting system be used to increase vaccine acceptance and trust?. Issue 21 (5th May 2016) - Scherer, Laura D.; Shaffer, Victoria A.; Patel, Niraj; Zikmund-Fisher, Brian J.
Abstract: Vaccine refusal has an impact on public health, and the human pappillomavirus (HPV) vaccine is particularly underutilized. Research suggests that it may be difficult to change vaccine-related attitudes, and there is currently no good evidence to recommend any particular intervention strategy. One reason for vaccine hesitancy is lack of trust that vaccine harms are adequately documented and reported, yet few communication strategies have explicitly attempted to improve this trust. This study tested the possibility that data from the vaccine adverse event reporting system (VAERS) can be used to increase trust that vaccine harms are adequately researched and that potential harms are disclosed to the public, and thereby improve perceptions of vaccines. In the study, participants were randomly assigned to one of three communication interventions. All participants read the Centers for Disease Control (CDC) vaccine information statement (VIS) for the HPV vaccine. Two other groups were exposed to additional information about VAERS, either summary data or full detailed reports of serious adverse events from 2013. Results showed that the CDC's VIS alone significantly increased perceptions of vaccine benefits and decreased perceived risks. Participants who were also educated about VAERS and given summary data about the serious adverse events displayed more trust in the CDC and greater HPV vaccine acceptance relative to the VIS alone. However, exposure to the detailed VAERS reports significantly reduced trust in the CDC and vaccine acceptance. Hence, general information about the VAERS data slightly increased trust in the CDC and improved vaccine acceptance, but the specific VAERS reports negatively influenced both trust and acceptance. Implications for communicating about vaccines are discussed.